Total Bakteri dan Kelimpahan Vibrio pada Budidaya Udang Vannamei (Litopenaeus vannamei) Sistem Resirkulasi Tertutup dengan Padat Tebar Berbeda - Bagus Anjasmara; Pande Gde Sasmita Julyantoro; Endang Wulandari Suryaningtyas (Current Trends in Aquatic Science, 2018)
Microbial management is one of the succesful keys on shrimp farming with high density and environtmental friendly culture system. This study was aimed at inversigation on abudance of total bacteria and Vibrio in vannamei shrimp culture using closed recircultion system with different stocking densities. This study used an experimental method with complete randomized design factorial and was performed with closed recirculation system equipped by bio-filters, protein skimmer, and using artificial feed with addition of probiotic. 9 ponds were used for this experiment including 3 control ponds (K) with 200 ind/m2 stocking density, 3 ponds I (P1) and 3 ponds II (P2) with 500 ind/m2 and 750 ind/m2 stocking density, respectively. Those 3 pond with similar stocking density represented as three times of repetition. After 60 days culture period, the average total bacteria and abundance of Vibrio collected from culture water of K, P1, and P2 ponds were 1,2 x 104, 1,6 x 105, and 2,1 x 104 CFU/mL and 1,2 x 103, 2,8 x 103, and 3,7 x 102 CFU/mL. Moreover, at he end of experiment, the average total bacteria and abundance of Vibrio collected from Shrimph body of K, P1, and P2 ponds were 2,7 x 106, 1,6 x 106, and 4,9 x 104 CFU/mL and 2,0 x 103, 1,4 x 103, and 8,5 x 102 CFU/mL. The statistical test of ANOVA was not significant (p> 0,05) between ponds.